Buah Plum Sebagai Pencegah Kejadian Preeklampsia Pada Kehamilan - Farhan Dzaki Alfahri (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Every year there are 10 million pregnant women who experience preeclampsia with the number of pregnant babies dying with preeclampsia reaching 500,000 babies year. Approximately 76,000 pregnant women died from preeclampsia and hypertension-related diseases. Preeclampsia is a blood pressure of at least 140 mmHg systolic or 90 mmHg diastolic at two tests corresponding to 15 minutes using the same with urine protein increased 300 mg in 24 hours or urine dipstick test> positive 1 and liver, neurological dysfunction. neurological, uteroplacental circulation, pulmonary edema, thrombocytopenia after 20 weeks of gestation. Preeclampsia is a pregnancy syndrome in the form of a lack of organ perfusion due to vasospasm and endothelial dysfunction. Increased capillary permeability, increased coagulation factors, increased vasopressor substances and decreased levels of vasodilators such as a nitric oxide (NO). One of the compounds that can increase NO levels is flavonoids which are found in plums. NO deficiency in pregnant women has an important role in the incidence of preeclampsia. Increased NO in pregnant women is being carried out to prevent preeclampsia. The content in plums has the function of increasing endothelial function and decreasing systolic and diastolic pressure. So that by eating plums can prevent the occurrence of preeclampsia in pregnancy.